Distribusi Phyllanthus emblica L. di Sumatera Utara Bagian Selatan - Ummi Khoiriyah; Nursahara Pasaribu; Saleha Hannum (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2015)
The Indian gooseberry (Phyllanthus emblica L.) distribution has been studied in the southern part of North Sumatera, which is in the South Labuhanbatu district, North Padanglawas, Padanglawas, SouthTapanuli, Padangsidempuan city and Mandailing Natal district. The aims ofthis study was to determine the distribution area of balakka based on rainfall, lands cover and soil type. The data were collectedby observation. Distribution data are presented in the  form of map using ArcView 3.3 Software. The results of the analysis showed that the common balakka was distributed in the rainfall region of 2000 – 2500 mm/year in dryland farming and the humic acrisols soil.